Oncogenic Viruses and Regulation by DNA Methylation - Jassim, Tabarak Sabah; Jihad, Noor A.; Torki, Sumyah H. (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
In order to avoid host defenses or maintain effective viral transmission as well as survival, viruses have developed a variety of strategies. Numerous DNA tumour viruses alter host DNA the enzymes methyl to cause epigenetic instability of hosting cells' immune-related genes regulation. Anti-tumor immune system responses were often associated with the host immunological mechanisms that were inhibited by virus-induced aberrant DNA methylation. In this instance, researchers discuss the processes including host-virus relationships that DNA tumor viruses utilize to control recipient Genome of their DNA with order to elude antimicrobial defense. This process might assist to create an immunological milieu that aids in the proliferation of malignancies. Positive outcomes are being seen in current immunotherapy investigations in treating various malignancies; yet, a considerable proportion of non-responders need the identification of new targeting for immunotherapy’s against cancer. Consequently, knowing how cancer-causing pathogens evade the immunological system could potentially reverse immunological reduction to avoid or cure related malignancies.